Expression of Idh1R132H in the murine subventricular zone stem cell niche recapitulates early gliomagenesis - Bardella, C; Al-Dalahmah, O; Krell, D; Brazauskas, P; Tomkova, M; Adam, J; Serres, S; Lockstone, H; Freeman-Mills, L; Pfeffer, I; Sibson, N; Goldin, R; et al. (Elsevier, 2016)
Isocitrate dehydrogenase 1 mutations drive human gliomagenesis, probably through neomorphic enzyme activity that produces D-2-hydroxyglutarate. To model this disease, we conditionally expressed Idh1^R132H in the subventricular zone (SVZ) of the adult mouse brain. The mice developed hydrocephalus and grossly dilated lateral ventricles, with accumulation of 2-hydroxyglutarate and reduced -ketoglutarate. Stem and transit amplifying/progenitor cell populations were expanded, and proliferation increased. Cells expressing SVZ markers infiltrated surrounding brain regions. SVZ cells also gave rise to proliferative subventricular nodules. DNA methylation was globally increased, while hydroxymethylation was decreased. Mutant SVZ cells over-expressed Wnt, cell cycle and stem cell genes, and shared an expression signature with human gliomas. Idh1^R132H mutation in the major adult neurogenic stem cell niche causes a phenotype resembling gliomagenesis.